2020
DOI: 10.3390/vibration3030022
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Assessment of Polynomial Nonlinear State-Space and Nonlinear-Mode Models for Near-Resonant Vibrations

Abstract: In the present article, we follow up our recent work on the experimental assessment of two data-driven nonlinear system identification methodologies. The first methodology constructs a single nonlinear-mode model from periodic vibration data obtained under phase-controlled harmonic excitation. The second methodology constructs a state-space model with polynomial nonlinear terms from vibration data obtained under uncontrolled broadband random excitation. The conclusions drawn from our previous work (experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…1). In comparison, phase resonance testing is not affected by the exciter's phase lag as long as the phase between measured excitation force and response is controlled (see [22,26] for similar simulated experiments using a PLL controller).…”
Section: Robustness Against the Phase Lag Induced By A Conventional E...mentioning
confidence: 99%
“…1). In comparison, phase resonance testing is not affected by the exciter's phase lag as long as the phase between measured excitation force and response is controlled (see [22,26] for similar simulated experiments using a PLL controller).…”
Section: Robustness Against the Phase Lag Induced By A Conventional E...mentioning
confidence: 99%
“…Mangan et al [19] have introduced model selection via sparse regression algorithms for linear-in-parameters problems. The polynomial nonlinear statespace (PNLSS) method [20,21] has also been used to select nonlinear models based on high order polynomials. However, different applications, such as the nonlinear identification of aero-engine structure [22], showed that the number of parameters included in the selected model by PNLSS is high and might not be parsimonious.…”
Section: Introductionmentioning
confidence: 99%